2020
DOI: 10.3390/rs12162621
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Earthquake-Damaged Buildings by Integrating UAV Oblique Photography and Infrared Thermal Imaging

Abstract: Extracting damage information of buildings after an earthquake is crucial for emergency rescue and loss assessment. Low-altitude remote sensing by unmanned aerial vehicles (UAVs) for emergency rescue has unique advantages. In this study, we establish a remote sensing information-extraction method that combines ultramicro oblique UAV and infrared thermal imaging technology to automatically detect the structural damage of buildings and cracks in external walls. The method consists of four parts: (1) 3D live-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Reported key areas on the use of UAVs post-disasters include aerial monitoring of damage evaluation, localisation of victims, SAR logistics and cargo delivery [8,9]. UAVs have also assisted through the rapid post-disaster assessment of damaged buildings after an earthquake [10,11], the custom design of defibrillator payloads [12,13] and the deployment of first aid kits in remote areas [14]. Recent research has also showed how UAVs can provide fast assessments on the identification of victims and their conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Reported key areas on the use of UAVs post-disasters include aerial monitoring of damage evaluation, localisation of victims, SAR logistics and cargo delivery [8,9]. UAVs have also assisted through the rapid post-disaster assessment of damaged buildings after an earthquake [10,11], the custom design of defibrillator payloads [12,13] and the deployment of first aid kits in remote areas [14]. Recent research has also showed how UAVs can provide fast assessments on the identification of victims and their conditions.…”
Section: Introductionmentioning
confidence: 99%
“…UAS imagery also provided detailed information about damaged structures, their structural material and components, as well as their failure mechanism (Adams et al 2014). Recently, Zhang et al (2020) proposed a four-step automatic building damage identification and information extraction technique using UAS-acquired oblique thermal images. After testing their system on earthquake-affected buildings, the authors advocated the usage of UASs for post-disaster assessment and showed that their method provided a damage detection accuracy of around 80%.…”
Section: Post-construction Applicationsmentioning
confidence: 99%
“…Histogram equalization [23,24] was used to enhance image gray resolution for crack detection [25] and crack monitoring from thermal imaging [26]. Wavelet transforms [27,28] were used to correct vision-based images for damage and crack detection [29,30] and fatigue crack detection [31]. Contrast enhancement was conducted on vision-based images to separate the crack and the background area [32], and the advanced deep learning method was capable of autonomously detecting concrete cracking, steel corrosion, and delamination [33].…”
Section: Introductionmentioning
confidence: 99%